Structural and Optical Properties of Fe₂O₃ Nanoparticles for Biosensing Applications - Hiba Fouad Tawfeeq Wali; Saja Abdul Ameer Sayed; Ahmed A.Thamer (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Nanostructured metal oxides are widely explored for sensing technologies due to their tunable structural and optical behavior. Specific Background: Iron oxide (Fe₂O₃), particularly hematite, offers stability, biocompatibility, and catalytic activity suitable for biosensing applications. Knowledge Gap: However, the combined structural–optical characterization of Fe₂O₃ synthesized via a simple sol–gel route and its integrated performance within a glucose biosensor remains insufficiently examined. Aims: This study investigates the structural, morphological, and optical properties of Fe₂O₃ nanoparticles and evaluates their functionality as an active layer in a glucose oxidase (GOx) sol–gel biosensor. Results: XRD confirmed hematite with sharp peaks at 33.2° and 35.7°, indicating high crystallinity; UV–Vis/Tauc analysis yielded a direct band gap of 2.1–2.2 eV; SEM/EDS revealed quasi-spherical aggregates composed predominantly of Fe and O. The biosensor exhibited first-order amperometric responses with T90 values of 26 s (2 mM) and 34 s (5 mM) and rapid T10 recovery ( 2 s). Novelty: The combination of sol–gel immobilization and Fe₂O₃’s intrinsic catalytic behavior produced fast, stable, and reversible glucose sensing. Implications: These findings support Fe₂O₃–sol–gel platforms as promising candidates for next-generation enzymatic biosensors. Highlights: Fe₂O₃ nanoparticles exhibit high crystallinity and a 2.1–2.2 eV direct band gap. Sol–gel Fe₂O₃–GOx biosensor achieves rapid response and recovery times. Demonstrates a synergistic catalytic–structural design for reliable glucose detection. Keywords: Fe₂O₃ Nanoparticles; Hematite; Glucose Biosensor; Optical Properties; Sol–Gel